Poetry Writing Ability As A Critical Thinking Representation Towards Social Reality of 9-A Students in SMPN 1 Kedungpring - Achmad Alwi Masyhuri; Khumaidi Abdillah; Sukiman Sukiman (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The research entitled “Poetry Writing Ability As A Critical Thinking Representation Towards Social Reality of 9-A Students In SMPN 1 Kedungpring” aims to describe the ability to write poetry in terms of the structure of poetry, interpretation of meaning, and the form of social reality that is displayed based on the level of complexity of meaning.. This research is a qualitative type with a descriptive method. Data collection was obtained from the students’ poetry anthology with a total 32 poems. Based on the results of the analysis of the ability to write poetry as a representation of critical thinking on social reality, there are 6 poems with low complexity of meaning, 15 poems of medium complexity of meaning, and 11 poems of high level of complexity of meaning. Keywords: representation, writing poetry ability, social reality, critical thinking Abstrak Penelitian yang berjudul “Kemampuan Menulis Puisi Sebagai Representasi Berpikir Kritis terhadap Realitas Sosial Siswa Kelas 9-A SMPN 1 Kedungpring” bertujuan untuk mendeskripsikan kemampuan menulis puisi ditinjau dari struktur pembangun puisi, interpretasi makna, dan bentuk realitas sosial yang ditampilkan berdasarkan tingkat kompleksitas makna. Penelitian ini adalah jenis kualitatif dengan metode deskriptif. Pengumpulan data diperoleh dari antologi puisi siswa dengan jumlah 32 puisi. Berdasarkan hasil analisis dari kemampuan menulis puisi sebagai representasi berpikir kritis terhadap realitas sosial, terdapat 6 puisi dengan kompleksitas makna rendah, 15 puisi tingkat kompleksitas makna sedang, dan 11 puisi pada tingkat kompleksitas makna tinggi. Kata kunci: representasi, kemampuan menulis puisi, realitas sosial, berpikir kritis